Dynamic multicoil technique (DYNAMITE) MRI on human brain. Issue 6 (16th June 2020) - Juchem, Christoph; Theilenberg, Sebastian; Kumaragamage, Chathura; Mullen, Michael; DelaBarre, Lance; Adriany, Gregor; Brown, Peter B.; McIntyre, Scott; Nixon, Terence W.; Garwood, Michael; de Graaf, Robin A.
Abstract : Purpose: Spatial encoding for MRI is generally based on linear x, y, and z magnetic field gradients generated by a set of dedicated gradient coils. We recently introduced the dynamic multicoil technique (DYNAMITE) for B0 field control and demonstrated DYNAMITE MRI in a preclinical MR environment. In this study, we report the first realization of DYNAMITE MRI of the in vivo human head. Methods: Gradient fields for DYNAMITE MRI were generated with a 28‐channel multicoil hardware arranged in 4 rows of 7 coils on a cylindrical surface (length 359 mm, diameter 344 mm, maximum 5 A per coil). DYNAMITE MRIs of a resolution phantom and in vivo human heads were acquired with multislice gradient‐echo, multislice spin‐echo, and 3D gradient‐echo sequences. The resultant image fidelity was compared to that obtained with conventional gradient coil technology. Results: DYNAMITE field control enabled the realization of all imaging sequences with average gradient errors ≤ 1%. DYNAMITE MRI provided image quality and sensitivity comparable to conventional gradient technology without any obvious artifacts. Some minor geometric deformations were noticed primarily in the image periphery as the result of regional field imperfections. The imperfections can be readily approximated theoretically through numerical integration of the Biot‐Savart law and removed through image distortion correction. Conclusion: The first realization of DYNAMITE MRI of the in vivo human head has been presented. The obtained image fidelity is comparable to MRI with conventional gradient coils, paving the way for full‐fledged DYNAMITE MRI and B0 shim systems for human applications.